The roles of consumers, farmers, and government toward development of organic product in Malaysia / Mohd Amirul Syafiq Abdul Rahman and Rasyidah Rasnin - Abdul Rahman, Mohd Amirul Syafiq; Rasnin, Rasyidah (2017)
This chapter focuses the background of the study, which is the organic product. It also emphasizes the incentive taken by the consumer, farmer and Government toward the Organic Food Production in Malaysia. The section 1.1 discusses the background of the study, section 1.2 explained the problem statement and section 1.3 states the research question, section 1.4 on the other hand state the research objectives and section 1.5 is on the information regarding the scope of the study. In additional section 1.6 explain the significance of the study and lastly section 1.7 is all about the definition in terms and concept.